Analisis Intensitas Konsumsi Energi (IKE) pada Institut Teknologi Dirgantara Adisutjipto (ITDA) Yogyakarta - Ndaru Atmi Purnami; Refni Arianti; Paulus Setiawan (Institut Teknologi Dirgantara Adisutjipto, 2022)
One of the main sectors that uses the largest electrical energy in a country is the commercial sector. One of the parts of this sector is education. This sector has a sub-sector. It is called a building. Electrical energy conservation efforts are needed to streamline electrical energy consumption by looking at energy-saving opportunities. This research was conducted at Halim Building and Wiweko Building in Institut Teknologi Dirgantara Adisutjipto (ITDA), Yogyakarta. The research was conducted by taking energy audit data regarding the level of electrical energy consumption as seen from the Energy Consumption Intensity (IKE) parameter. The research method began with the data collection. Furthermore, the data were processed using Ms. Excel, SPSS, and Matlab. Statistics analysis with ANOVA was carried out to conclude what parameters affected IKE. The results showed that the IKE value of the Halim Building was 30,48 kWh/m2/year and the IKE value of the Wiweko Building was 24,16 Wh/m2/year. The IKE value was still significant in the efficient category following ESDM & JICA Electric Power Development Co. LTD standards.